Strategic Green Ergonomics Design to Enhance Eco-Campus Effectiveness in Higher Education Institutions for Sustainability Outcomes - Ida Kusnawati Tjahjani; Yunia Dwie Nurcahyanie; Sri Widyastuti; Manik Ayu Titisari; Sabrina Nur Saraswati; Alexander Indra Putra Hartawan (Environmental Pollution Journal, 2026)
The effectiveness of the eco-campus program remains suboptimal due to weak integration among environmental, behavioral, and ergonomic aspects of campus users. This research aims to design strategies to enhance the effectiveness of the eco-campus program at Universitas PGRI Adi Buana Surabaya through a green ergonomics approach. Data were collected through observation, questionnaire distribution, and interviews involving all members of the academic community. The data were identified using a Fishbone Diagram and analyzed using the SWOT method to determine internal and external factors, followed by the formulation of improvement strategies using the QSPM method.The results of the study produced four strategies, namely S1, S2, S3, and S4. The prioritized strategy is S1—an Integrated Green Ergonomics Model—with the highest total score of 3.60. Therefore, it is necessary to increase the total attractiveness scores of the following factors: dependence on expensive technology (T3), lack of national Green Ergonomics standards (T4), changes in internal leadership policies (T2), resistance to organizational cultural change (T1), low awareness of the academic community regarding Green Ergonomics (W2), limited budget and management priorities (W4), support for sustainable research grants (O3), and the lack of cross-unit integration in eco-campus implementation (W1).